Cervical spine mechanical deficits in patients with shoulder impingement syndrome: A case-control study - Fatma Eldesoqi Ramadan El-desoqi; Salwa Fadl Abdal Majeed; Ahmad Hamdy Azzam; Mohammed Ali Mohammed Sarhan (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.